Studi terhadap pergaulan lintas agama dalam meningkatkan kearifan sosial mahasiswa di IKIP Budi Utomo Malang - Kurniawan, Choirul; Tobing, Melliana Sari; Zaini, Moh. (Publisia: Jurnal Ilmu Administrasi Publik, 2018)
Social interactions in everyday life are commonplace and occur naturally. But not automatically the guarantee that the association without giving birth to conflict, on the contrary, the existing naturality has the potential to create a 'sensitive space' of various diversity; ethnicity, culture, even religion. In the context of student interfaith relationships, occupy sensitive positions. This lies in the 'taboo' of students in discussing 'issues' of religious differences. If this is the reality, then one day the 'taboo' will become a deadlock center, thus hampering the process of socializing (social intercourse). This will not only cause a culture of silant, more than that it can also cause social conflict, so that it will affect social harmony across religions within the scope of the education association between students at the IKIP Budi Utomo Malang. Activities that will be carried out are analyzing cross-religious social relations of students at IKIP Budi Utomo Malang, with the aim of finding patterns of interfaith social relations among students, and offering an offer of social concepts of student interfaith intercultural engineering, so that religious social (social) wisdom at the student level becomes better. The approach used is a qualitative-phenomenological research approach, using the instrument indept interview, documentation, and observation / participants. The analysis model that will be used is the Miles and Huberman analysis model: data collection, data display, data reduction and congclusions: drawing / verifying. While the grand theory used in this study is to use sociological theories of religion.Â